(3GdQbGHI GdeGdjI aj GdfXGe GdGbJUGOj GdGSdGej (B/s - (3YjGUQI, HSGe YhV YHO GdQMjes ((3YeGf(B: s (3OGQ GdMGeO(B, s, 2010)
(3JYQja GdQbGHI GdeGdjI , eTQhYjJgGaj GdfXGe GdGbJUGOj GdGSdGej , GdQbGHI GdeGdjI aj UOQ GdGSdGe h JWhQgG, GgOGagG , eRGjGgG h GdbGFehf HgG aj GdfXGe GdGbJUGOj GdGSdGej , GdQbGHI GdeGdjI Ydi GdGjQGOGJ GdYGeI h fabGJgG aj GdfXGe GdGbJUGOj GdGSdGej h CfhGYgG ef MjK GdJhbjJ h ef MjK GdLgI OhQ GdNdjaI h GdhRjQ h GdOhGhjf aj GdQbGHI GdeGdjI , HjJ GdeGd h fXGe GdMSHI hhdGjI GdeXGde hOhQge aj GdQbGHI GdeGdjI (B.s
(3eQGLY U(B.237s
Keywords: (3GdGbJUGO GdGSdGejs; (3GdQbGHI GdeGdjIs; (3JObjb GdMSGHGJs